Efektifitas Penyelesaian Mediasi dalam Perkara Perdata di Pengadilan Berdasarkan Perma No. 1 Tahun 2016 - Christian Bellarminus Fradinata; Hery Firmansyah (CV Rewang Rencang, 2025)
This research analyzes the effectiveness of the implementation of Supreme Court Regulation (PERMA) no. 1 of 2016 in resolving civil cases at the Denpasar District Court Class IA through mediation. The research uses empirical legal methods, with a statutory approach to analyze legal principles and a factual approach to describe the practical implementation of mediation. Data was obtained through interviews, observations and document studies, and analyzed descriptively qualitatively to understand the empirical reality, views and constraints from various perspectives, including judge mediators, disputing parties and private mediators. The research results show that although mediation increases the efficiency of the dispute resolution process, its success is still low compared to the number of cases submitted, due to the limited number of certified mediators and lack of public understanding. Recommendations include increasing mediator training, outreach on the benefits of mediation, and adoption of technology to increase efficiency and accessibility.